Pengaruh E-Customer Satisfaction Dan E-Customer Trust Terhadap Online Repurchase Intention Pada Marketplace Shopee - Andriansyah; Dayat Ikhsan H (JURNAL BISNIS DAN PEMBANGUNAN, 2024)
Abstract: The purpose of this final project is to find out whether E-Customer Satisfaction and E-Customer Trust affect the Online Repurchase Intention or the intention to repurchase Shopeeconsumers. In this study the authors used quantitative research methods. The sampling techniqueused is purposive sampling with a sample of 385 people obtained based on the Rao Purba formulabecause the total population is not known with certainty. Data collection techniques using onlinequestionnaires through google forms that have been tested for validity and reliability. The dataanalysis technique used is the classical assumption test, multiple linear regression analysis, andhypothesis testing with SPSS version 25 software.The results of this study indicate that e-customer satisfaction (X1) has a tcount value of10,557, where the tcount value is greater than the ttable value, which is 1,966 with a significancevalue of 0.000 <0.05, which means that e-customer satisfaction has a positive influence and alsosignificant to Online Repurchase Intention. E-trust (X2) has a tcount value of 5.846, where the ttablevalue is 1.966 with a significance value of 0.000 <0.05, which means that e-customer trust has apositive and significant influence on Online Repurchase Intention. The Fcount value obtained is402,384, where the Fcount value is greater than the Ftable value, which is 2.62, which means thate-customer satisfaction and e-customer trust together have a positive and significant effect on OnlineRepurchase Intention